PREDICTABILITY OF D-DIMER LEVEL ON ADMISSION FOR HOSPITAL OUTCOMES IN HOSPITALIZED PATIENTS WITH COVID-19 PNEUMONIA - Markovska, Zorica; Stavridis, Sotir; Mijakoski, Dragan; Panovska Stavridis, Irina; Meshkova, Iskra; Stoleski, Sasho; Stojanoski, Ivica; Lazova, Evgenija (University Ss. Cyril and Methodius in Skopje, 2022)
The aim of this study was to evaluate the role of D-dimer as a biomarker in the assessment of COVID-19 prognosis in hospitalized patients. Material and methods: A total of 117 patients with confirmed COVID-19 pneumonia between the age of 19 and 89 years (mean age 53) were admitted to the City General Hospital 8th September, Skopje, Macedonia. In all patients, a D-dimer test for coagulation profile and lactate dehydrogenase (LDH) for disease progression were performed on the day of admission. Patient demographic data, presence of comorbidities, severe symptoms, and radiological findings were determined for each patient. We calculated the National Early Warning Score (NEWS 2) for assessment of acute illness severity. The level of oxygen saturation (SpO2) was also determined. Length of hospital stay and length of stay at home were filled later after hospitalization using medical records. Results: Patients were classified according to D-dimer level into a low group (D-dimer ≤ 2 mcg/ml) and a high group (D-dimer ≥ 2 mcg/ml). Elevated D-dimer level was associated with severity, hypoxia, and lethal outcome. Patients with a high level of D-dimer had a higher NEWS 2 score, worsen radiological findings, and higher LDH. Patients with low levels of D dimer stayed at home longer than those with higher D-dimer levels. Conclusion: The D-dimer level is a useful marker in assessing the coagulation profile of patients with COVID-19 pneumonia regardless of the type of disease. Implementation of screening tools like the NEWS 2 score is also needed for better risk stratification on hospital admission.
Keywords: D dimer; Covid-19 pneumonia; News2 score